Genetic Characterization and Comparison of Clostridium botulinum Isolates from Botulism Cases in Japan between 2006 and 2011 - Kenri, Tsuyoshi (Appl Environ Microbiol, 2014)
Genetic characterization was performed for 10 group I Clostridium botulinum strains isolated from botulism cases in Japan between 2006 and 2011. Of these, 1 was type A, 2 were type B, and 7 were type A(B) {carrying a silent bont/B [bont/(B)] gene} serotype strains, based on botulinum neurotoxin (BoNT) production. The type A strain harbored the subtype A1 BoNT gene (bont/A1), which is associated with the ha gene cluster. The type B strains carried bont/B5 or bont/B6 subtype genes. The type A(B) strains carried bont/A1 identical to that of type A(B) strain NCTC2916. However, bont/(B) genes in these strains showed single-nucleotide polymorphisms (SNPs) among strains. SNPs at 2 nucleotide positions of bont/(B) enabled classification of the type A(B) strains into 3 groups. Pulsed-field gel electrophoresis (PFGE) and multiple-locus variable-number tandem-repeat analysis (MLVA) also provided consistent separation results. In addition, the type A(B) strains were separated into 2 lineages based on their plasmid profiles. One lineage carried a small plasmid (5.9 kb), and another harbored 21-kb plasmids. To obtain more detailed genetic information about the 10 strains, we sequenced their genomes and compared them with 13 group I C. botulinum genomes in a database using whole-genome SNP analysis. This analysis provided high-resolution strain discrimination and enabled us to generate a refined phylogenetic tree that provides effective traceability of botulism cases, as well as bioterrorism materials. In the phylogenetic tree, the subtype B6 strains, Okayama2011 and Osaka05, were distantly separated from the other strains, indicating genomic divergence of subtype B6 strains among group I strains.